Research of hemoparasites in ticks collected from dogs resident in the municipality of Itu, São Paulo, SP - Carvalho, Tânia; Andrade, Paula; Moraes Filho, Jonas (Brazilian Journal of Global Health, 2022)
OBJETIVO: Objetivou-se nesse estudo relatar a ocorrência de Ehrlichia canis, Babesia canis vogeli e Rangelia vitalli, em carrapatos coletados em cães residentes no município de Itu_São Paulo/SP, Brasil. MÉTODOS: Foi realizada a extração de DNA de 200 amostras de carrapatos com o “kit” de extração “PureLink Genomic DNA Kit” (Invitrogen®) e realizada a PCR em tempo real para a detecção de Ehrlichia canis, Rangelia vitalli, Babesia canis vogeli. RESULTADOS: Foram testados 200 carrapatos, sendo 1/200 (0,5%) da espécie do gênero Amblyomma aureolatum e 199/200 (99,5%) de Rhipicephalus sanguineus. Os resultados mostram uma taxa de ocorrência de positividade apenas em R. sanguineus, sendo de 0,5% (1/200) para E. canis; 41% (82/100) para B. c. vogeli. Nenhum carrapato foi positivo para R. vitalli. CONCLUSÃO: A detecção de B. canis vogeli e E. canis em carrapatos coletados em cães residentes no município de Itu, no Estado de São Paulo, Brasil; mostram a dispersão destes agentes patogênicos no país e o papel do R. sanguineus s.l. como vetor destes patógenos não pode ser negligenciado. DESCRITORES: Ehrlichia canis, Babesia canis vogeli, Rangelia vitalli, Carrapatos. ABSTRACT OBJECTIVE: The aim of this study was to report the occurrence of Ehrlichia canis, Babesia canis vogeli and Rangelia vitalli in ticks collected from dogs living in the city of Itu_São Paulo/SP, Brazil. METHODS: DNA was extracted from 200 tick samples using the extraction kit PureLink Genomic DNA Kit (Invitrogen®) and real-time PCR was performed for the detection of Ehrlichia canis, Rangelia vitalli and Babesia canis vogeli. RESULTS: We tested 200 ticks, 1/200 (0.5%) of the genus Amblyomma aureolatum and 199/200 (99.5%) of Rhipicephalus sanguineus. The results show an occurrence rate of positivity only in R. sanguineus, being 0.5% (1/200) for E. canis; 41% (82/100) for B. c. vogeli. No ticks were positive for R. vitalli. CONCLUSION: The detection of B. canis vogeli and E. canis in ticks collected from dogs living in the municipality of Itu, São Paulo State, Brazil; show the dispersion of these pathogens in the country and the role of R. sanguineus s.l. as a vector of these pathogens cannot be neglected. DESCRIPTORS: Ehrlichia canis, Babesia canis vogeli, Rangelia vitalli, Ticks.